Combined photothermal–photodynamic therapy by indocyanine green loaded polydopamine nanoparticles enhances anti-mammary gland tumor efficacy. Issue 24 (1st June 2022) - Liu, Xu; Xu, Na; Pu, Ximing; Wang, Juan; Liao, Xiaoming; Huang, Zhongbing; Yin, Guangfu
Abstract : We developed novel ICG loaded polydopamine nanoparticles with a hyaluronate outer layer. The nanoparticles exhibited excellent photothermal conversion capacity and efficient singlet oxygen production. IIPH could significantly inhibit the growth of tumors by PTT–PDT. Abstract : Various nano-targeted drug delivery systems have been developed for combined photothermal–photodynamic (PTT–PDT) treatment of tumors due to better outcomes compared with monomodality therapy. Here, we constructed a facile two-step method without core templates to obtain indocyanine green (ICG) loaded-hyaluronic acid (HA) surface-coated polydopamine nanoparticles (IIPH). The prepared nanoparticles demonstrated an excellent photothermal conversion capacity and efficient singlet oxygen production. Both in vitro and in vivo studies proved that IIPH could significantly inhibit the growth of tumor by PTT–PDT combinational treatment. All the results indicated that IIPH NPs hold great potential to be utilized as a new photothermal–photodynamic composite for cancer treatment.